Agronomic performance of common bean cultivars under irrigation levels assessed by spectral indices and modeling - Coelho, Anderson Prates [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In tropical and subtropical regions of Brazil, the cultivation of common bean can be carried out throughout the year, but it is subject to high variability in climatic conditions. Associated with this are factors such as irrigation, fertilization, and type of cultivars and the technological degree of the farms which also contribute to increasing the variability in crop yield. Studies on these factors and techniques to explain these variations are required to generate specific recommendations in this context. A two-year field experiment was conducted in the winter season in the Southeastern part of Brazil to evaluate, explain, and model the effect of irrigation levels on grain yield, technological and nutritional quality of grains, extraction and export of macronutrients, and define the level of irrigation and the sowing time that provide the best agronomic performance, using the CSM-CROPGRO-Dry bean model, in common bean cultivars with contrasting growth habits. Additionally, the potential application of spectral indices (NDVI and chlorophyll index - LCI) to forecast the yield of common bean cultivars was evaluated. The cultivars IAC Imperador (determinate growth and early cycle) and IPR Campos Gerais (indeterminate growth and normal cycle) were used in this study. These cultivars were subjected to five irrigation levels (54%, 70%, 77%, 100%, and 132% of crop evapotranspiration). Water deficit reduced the common bean agronomic performance, regardless of the cultivar. Furthermore, the water deficit reduced the technological and nutritional quality of the grains and the accumulation of macronutrients and anticipated the maximum daily demand for most macronutrients. IPR Campos Gerais showed better agronomic performance, efficiency, and response to water use than IAC Imperador, in addition to higher technological and nutritional quality and greater accumulation of biomass and macronutrients. Moreover, the maximum daily nutrient demand of cultivar IAC was anticipated compared with that of IPR. The CSM-CROPGRO-dry bean model showed high accuracy in estimating the growth and yield of the evaluated cultivars. Based on the long-term analysis in the model, it was observed that it is possible to manage irrigation with a controlled water deficit without significantly reducing the common bean yield if sowing is anticipated (March-April) within the winter crop. The meteorological element that most interfered with common bean yield was the global solar radiation (GSR) after the flowering of the crop, in which each unit increment in the GSR generated increments in the grain yield (GY) of the cultivars IAC and IPR by 55 and 50 kg ha-1, respectively. It was possible to forecast the GY of common bean cultivars (R2 = 0.64; RMSE= 370 kg ha-1; MBE= -140 kg ha-1) from the NDVI, both in individual models by cultivar and in the general model, whereas for the LCI, the accuracy was lower (R2 < 0.40; RMSE > 650 kg ha-1; MBE > 450 kg ha-1). These results demonstrate that the definition of more specific management is essential to increase sustainability in areas cultivated with common bean, helping to optimize the use of water and nutrients, sowing dates, and the application of remote sensing in cultivars with contrasting growth habits.

Em regiões tropicais e subtropicais, como no Brasil, o cultivo do feijão-comum pode ser realizado durante todo o ano, sendo submetido a elevadas variabilidades de condições climáticas. Associado a isso, fatores como, o manejo de irrigação e adubação, a cultivar utilizada e o nível tecnológico dos produtores também contribuem para aumentar a variabilidade de cultivo. Nesse contexto, estudos que envolvam esses fatores e técnicas para explicar essas variações são necessários para gerar recomendações mais específicas. Através de um experimento de dois anos agrícolas na safra de inverno no Sudeste do Brasil, esse estudo objetivou avaliar, explicar e modelar o efeito de níveis de irrigação sobre a produtividade de grãos, qualidade tecnológica e nutricional dos grãos, extração e exportação de macronutrientes e definir o nível de irrigação e a época de semeadura que proporcione o melhor desempenho agronômico, utilizando o modelo CSM-CROPGRO-Dry Bean, em cultivares de feijão-comum com hábitos de crescimento contrastantes, além de avaliar a aplicação de índices espectrais (NDVI e índice de clorofila) para a previsão da produtividade do feijão-comum. Foram utilizadas as cultivares IAC Imperador (crescimento determinado e ciclo precoce) e IPR Campos Gerais (crescimento indeterminado e ciclo normal). Essas cultivares foram submetidas a cinco níveis de irrigação (54, 70, 77, 100 e 132% da evapotranspiração da cultura). O déficit hídrico reduziu o desempenho agronômico do feijão-comum, independentemente da cultivar. Além disso, o déficit hídrico reduziu a qualidade tecnológica e nutricional dos grãos, o acúmulo de macronutrientes e antecipou a máxima demanda diária para a maioria dos macronutrientes. Entre cultivares, a IPR apresentou desempenho agronômico e eficiência e resposta ao uso da água superiores a cultivar IAC, além de maior qualidade tecnológica e nutricional e maior acúmulo de biomassa e macronutrientes. Além disso, a máxima demanda diária de nutrientes da cultivar IAC foi antecipada em relação a IPR. O modelo CSM-CROPGRO-Dry bean apresentou elevada acurácia na estimativa do crescimento e produtividade das cultivares avaliadas. A partir da análise de longo período no modelo, observou-se que é possível manejar a irrigação com déficit hídrico controlado sem reduzir significativamente a produtividade do feijão-comum, desde que a semeadura seja antecipada (mar/abr) dentro da safra de inverno. O elemento meteorológico que mais interferiu na produtividade do feijão foi a radiação solar global (RSG) após o florescimento da cultura, em que cada incremento unitário na RSG gerou incrementos na PG das cultivares IAC e IPR aumentam em 55 e 50 kg ha-1, respectivamente. Foi possível prever a PG das cultivares de feijão-comum (R2= 0,64; RMSE= 370 kg ha-1; MBE= -140 kg ha-1) a partir do NDVI, tanto em modelos individuais por cultivar quanto pelo modelo geral, enquanto para o ICF a acurácia foi menor (R2< 0,40; RMSE> 650 kg ha-1; MBE> 450 kg ha-1). Esses resultados demonstram que a definição de manejos mais específicos é fundamental para aumentar a sustentabilidade no cultivo de feijão-comum, auxiliando na otimização de uso da água, nutrientes, datas de semeadura e aplicação de sensoriamento remoto em cultivares contrastantes.
Desempenho agronômico de cultivares de feijão-comum sob níveis de irrigação, avaliado por índices espectrais e modelagem
Keywords: Common beans; Irrigation; Models; Nutrient requirements; Remote sensing